ANALISIS TERHADAP PERANAN DAN STRATEGI BANK INDONESIA SERTA PEMERINTAH DALAM MENJAGA STABILITAS SISTEM KEUANGAN DI INDONESIA - Dian Indah Sari (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2015)
Instability of  the financial system is very bad impact is the loss of public confidence and declining economic growth and community. Besides the cost of economic recovery particularly the financial sector is very large due to the crisis. While the recovery process also runs less in line with expectations. Therefore, the stability of the financial system must be maintained to ensure the public interest. Research methods used  is the method of content analysis by describing and analyzing the existing sources to record these data relate to each other the problem studied. Role of Bank Indonesia in maintaining the the stability of the financial system, among others maintain monetary stability, creating a healthy performance of financial institutions, organize and maintain smooth operation of payment systems, research and monitoring and financial system safety net. strategy of Bank Indonesia in maintaining the the stability of the financial system, among others coordination and cooperation, monitoring, crisis prevention and crisis management. There are three reasons for the importance of the stability of the financial system, namely: monetary stability can only be realized with the financial stability, a stable financial system will creating trust and supportive environment for depositors and investors, encourage efficient financial intermediation, encourage the operation of the market and improve the allocation of economic resources. Bank Indonesia and government has implemented its role and strategy in maintaining the stability of the financial system in Indonesia.  Keywords : Role, Strategy, Stability of Financial System